Efficacy of Panniculectomy with Cesarean Section - Neama Anwar; Abd Elraouf Oun; Mahmoud Amin; Ahmed Elshorbagy (International Journal of Medical Arts, 2023)
Background: A panniculectomy helps contouring the abdomen by removing the panniculus. Patients with large overhanging abdominal panniculus should benefit from this treatment. Pregnancy changes the size and contour of the abdomen; so, abdominoplasty is often requested during a Cesarean delivery. In late pregnancy, especially in multiparous women, the abdominal wall muscles are subjected to increased strain, and the rectus muscles divaricate in the midline, generating diastasis recti. Panniculectomy is a popular women's aesthetic surgery. It can be long-lasting if maintained with exercise and a balanced diet.Aim of the work: The goals of this study are to assess the advantages, disadvantages, cosmetic outcomes, and complications of combining panniculectomy with Caesarean Section.Patients and Methods: A prospective randomized clinical controlled trial where 50 of Gravid women shared and equally distributed to two groups, each group includes 25 pregnant women who had already made the decision to have an elective Cesarean section at Al-Azhar University's Department of Obstetrics and Gynecology.Results: In terms of time needed to complete a procedure, there was a massive gap between the two groups. The two groups did not differ significantly with respect to wound complications, post-operative body mass index. The Panniculectomy with CS group had a mean of 8.72 ± 1.24. [range: 5-10] in terms of patient satisfaction.Conclusion: There's an argument that doing both operations at once would save time and money. It does not appear to be in the best interests of most patients, however, due to the higher risk of postoperative complications and un-esthetic outcomes. More research is needed to determine how the surgery affects long-term recovery, future obstetric outcomes, and other medical issues.